Pengaruh Beban Kerja dan Sistem Shift Kerja terhadap Motivasi Kerja Karyawan Operasional dalam Mendukung Kualitas Layanan Hotel - Keylla Nursita Dwi Ayunda; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the influence of workload and shift work systems on the work motivation of operational employees in supporting service quality at Hotel Tentrem Semarang. The problem is focused on how workload balance and the effectiveness of shift work arrangements influence motivation as a key determinant of service performance. To address this issue, the study adopts theoretical perspectives from work motivation theory, workload theory, as well as ergonomics and organisational behaviour theory that emphasise employee well-being. Data were collected through a five-point Likert scale questionnaire distributed to 75 operational employees and analysed quantitatively using multiple linear regression. The results indicate that workload has a positive effect on work motivation, while the shift work system has a more dominant influence in shaping employee motivation. Both variables simultaneously explain 41% of the variation in work motivation, highlighting the strategic role of operational work management in enhancing motivation. Theoretically, this study strengthens the integration between ergonomic factors and work motivation within the hospitality industry context. Practically, the findings imply that designing proportional workloads and adaptive shift systems is essential for improving employee motivation and maintaining consistent service quality.